Ubiquitination in macrophage plasticity: from inflammatory to immunometabolic pathways - Liu, Jianing; Paolino, Magdalena (Frontiers in Immunology, 2025)
Macrophages are highly plastic innate immune cells whose polarization and effector functions are tightly linked to their metabolic programs. Ubiquitination, the post-translational modification that attaches ubiquitin chains to target proteins, plays a crucial role in regulating macrophage immunometabolism and phenotype transitions. In this mini-review, we summarize the current understanding of ubiquitin-dependent mechanisms that modulate macrophage polarization. We discuss how E3 ubiquitin ligases and deubiquitinases regulate key metabolic and signaling pathways, balancing pro-inflammatory and immunosuppressive states. Additionally, we describe the pathophysiological consequences of dysregulated ubiquitin-dependent control of macrophage polarization and its implications for disease. These insights underscore the importance of ubiquitination as a central modulator of macrophage function and its potential as a therapeutic target for controlling immunity in infections, inflammation, and cancer.